DNA Damage in Human Amniotic Cells: Antigenotoxic Potential of Curcumin and α-Lipoic Acid - Filomena Mottola; Marianna Santonastaso; Concetta Iovine; Cristina Rossetti; Valentina Ronga; Lucia Rocco (MDPI AG, 2021)
Oxidative imbalances in the gestational phase are responsible for certain complications during pregnancy and for foetal and neonatal genetic disorders. In this work, using human amniocytes, we aimed to evaluate the protection provided to foetal DNA by two concentrations of antioxidant molecules, α-lipoic acid (LA) and curcumin (Cur), against hydrogen peroxide (H2O2)-induced damage. Genotoxicity tests, performed by the random amplification of polymorphic DNA (RAPD-PCR) technique and TUNEL tests, showed that the lowest concentration of LA-protected cells and DNA from H2O2 insults. However, a greater ability to protect the amniocytes' DNA against H2O2 was observed following co-treatment with the highest concentration of Cur with H2O2. In fact, a genomic template stability (GTS%) similar to that of the negative control and a statistically significant reduction in the DNA fragmentation index (DFI) were revealed. Moreover, following a combined treatment with both antioxidants and H2O2, no statistical difference from controls was observed, in terms of both induced mutations and DNA breaks. Furthermore, no effect on morphology or cell viability was observed. The results demonstrate the ability of LA and Cur to protect the genetic material of amniocytes against genotoxic insults, suggesting their beneficial effects in pathologies related to oxidative stress.